A case study on dynamic capabilities developed by a product start-up to grow at the time of pandemic. Issue 2 (3rd April 2022) - Chakrabarti, Dipankar; Mukherjee, Arindam
ABSTRACT: Business operations became challenging when the COVID-19 pandemic struck, and governments applied significant lockdown measures to stop the spread. Start-ups and small-medium businesses started facing hardships due to the changes in the business environment and the resulting constricted cash flow. This case describes challenges faced by a high-tech product start-up company and the way they tackled these hardships. The company had adopted an agile programming methodology for product development which faced a major challenge because of the sudden introduction of "work from remote" (WFR). WFR had disrupted collaboration between clients, sales teams, and development teams. The success of agile methodology was dissipating as teams could not do on-premise huddles. The company witnessed an overrun in the sprint schedule, increase of budgeted cost, and sliding customer satisfaction. Senior management could not manage process parameters properly, and therefore predictability of the processes waned. The start-up owners, through the application of the "dynamic capabilities framework, " focused on reconfiguring the agile working processes and improving the remote working capability of employees. This case shows the start-up's agile development process transformation journey following the dynamic capabilities framework to overcome the challenges posed by the pandemic. The teaching case focuses on imparting knowledge on agile development and dynamic capabilities to Information Systems students.